HUBUNGAN ANTARA KELINCAHAN, KELENTUKAN DAN DAYA LEDAK TERHADAP HASIL SMASH KEDENG SEPAK TAKRAW PADA MAHASISWA PUTRA PJKR KELAS D ANGKATAN 2018 UNIVERSITAS TADULAKO - Sardiman .; Haeruddin . (Jurnal Ilmu Pendidikan Jasmani Kesehatan Dan Olahraga, 2020)
The purpose of. The data collection technique used was the research data collected through four activities or four measurement stages, namely: agility test, flexibility test, explosive power test, smash test ability in the game Sepak Takraw. The results of this study indicate that there is a significant relations. agility, togok flexibility and explosive power on the results of the kedeng smash at Sepak takraw. From the results of the data analysis obtained, two things are shown. First, the significant value for the variables agility, flexibility and explosive power on the results of the soybean smash obtained is 0.009. Second, the significant value obtained is less than 0.05 (0.009 <0.05). The assumptions that can be put forward by the author here are that agility, flexibility and explosiveness have a relationship to the results of the kedeng smash in male students of PJKR class D 2018, Tadulako University, because the significant value obtained is less than 0.05 in other words, the results of this study "There is a relationship of agility, flexibility and explosive power to the results of the smash for male PJKR class D students of 2018, Tadulako University".